Urban spaces and urban life in Örestad South - Palmlund, Martin (2007)
This master thesis is a result of the work thas was done for my entry in the international architectural competition Urban spaces and urban life in Ørestad South, that was announced by Ørestadselskabet on the 31st of October 2006. The project work lasted from early November until the deadline on 14th of February. In addition to the proposal that was handed in, the master thesis consists of a number of reflections about the work that was done and design work in general.